Early development, stress and depression across the life course: pathways to depression in a national British birth cohort. Issue 13 (27th February 2014) - Colman, I.; Jones, P. B.; Kuh, D.; Weeks, M.; Naicker, K.; Richards, M.; Croudace, T. J.
Abstract : Background: The aetiology of depression is multifactorial, with biological, cognitive and environmental factors across the life course influencing risk of a depressive episode. There is inconsistent evidence linking early life development and later depression. The aim of this study was to investigate relationships between low birthweight (LBW), infant neurodevelopment, and acute and chronic stress as components in pathways to depression in adulthood. Method: The sample included 4627 members of the National Survey of Health and Development (NSHD; the 1946 British birth cohort). Weight at birth, age of developmental milestones, economic deprivation in early childhood, acute stressors in childhood and adulthood, and socio-economic status (SES) in adulthood were assessed for their direct and indirect effects on adolescent (ages 13 and 15 years) and adult (ages 36, 43 and 53 years) measures of depressive symptoms in a structural equation modelling (SEM) framework. A structural equation model developed to incorporate all variables exhibited excellent model fit according to several indices. Results: The path of prediction from birthweight to age of developmental milestones to adolescent depression/anxiety to adult depression/anxiety was significant ( p < 0.001). Notably, direct paths from birthweight ( p = 0.25) and age of developmental milestones ( p = 0.23) to adult depression were not significant. Childhood deprivation and stressors had important direct and indirect effects on depression. Stressors in adulthood were strongly associated with adult depression. Conclusions: Depression in adulthood is influenced by an accumulation of stressors across the life course, including many that originate in the first years of life. Effects of early-life development on mental health appear by adolescence.